Minimally invasive surfactant therapy in preterm infants: towards less invasive management - Meireles,Daniel (2021)
Abstract Introduction: Minimally invasive surfactant therapy (MIST) is a surfactant administration procedure that intends to reduce intubations and associated risks. The aim of this study was to compare MIST with INtubation-SURfactant-Extubation (INSURE) technique. Material and methods: Retrospective analysis (from January 2015 to June 2019) of preterm infants on nasal continuous positive airway pressure (nCPAP) treated with surfactant. Results: Fifty-four preterm infants were included and divided in two groups: MIST (n=34) and INSURE (n=20). No significant differences were found between groups regarding gestational age (p=0.480), birth weight (p=0.299), fraction of inspired oxygen (FiO2) prior to surfactant (p=0.220), oxygen therapy duration (p=0.306), progression to intubation (p=0.712), or length of Neonatal Intensive Care Unit stay (p=0.778). FiO2 variation before and after surfactant administration was higher in MIST group (14% vs 9%, p=0.078). No significant complications were reported with either technique. Conclusions: MIST is a safe technique in preterm infants on nCPAP. This study shows similar outcomes with MIST and INSURE procedures, with a greater reduction in FiO2 requirements with MIST. Overall, MIST is less invasive and as effective as INSURE in preterm infants.